Leading Sectors and World Powers: The Coevolution of Global Economics and Politics, George Modelski y W illiam R. Thompson, University of South Carolina Press, 1996, 280 páginas. - Lemarchand, Guillermo (1997)
Fil: Lemarchand, Guillermo A. Universidad de Buenos Aires. Centro de Estudios Avanzados; Argentina.